DEVELOPING A LEARNING MODULE OF COMPUTER NUMERICALLY CONTROL GSK 983 MACHINES TO ENHANCE STUDENTS’ LEARNING OUTCOMES - Martono, Martono; Wagiran, Wagiran (Jurnal Pendidikan Teknologi dan Kejuruan, 2016)
This study aims at: (1) producing a learning module of Computer Numerically Control (CNC) GSK 983 machines to enhance the students’ learning outcomes, (2) investigating the learning process of CNC GSK 983 machines in vocational schools, (3) analyzing the effectiveness of the developed module in vocational schools. This study refers to the research procedure of design and development by Richey and Klein consisting of (1) observations of learning and products development, (2) internal and external validation, and (3) testing the effectiveness of the product in the field. The data was analyzed using T-Test. The results showed that: (1) the CNC learning outcomes in Vocational Schools did not meet the expectation; (2) learning modules of CNC GSK 983 to enhance the students’ learning outcomes was developed, and (3) the developed module was effective to enhance the students’ learning outcomes. The results of the t-test showed that there was a significant difference between the learning outcomes with the module and the learning outcomes without the module. It means that the module can improve the students’ learning outcomes.